White adipose tissue cells and the progression of cachexia: inflammatory pathways. Issue 2 (7th July 2015) - Neves, Rodrigo X.; Rosa‐Neto, José Cesar; Yamashita, Alex S.; Matos‐Neto, Emidio M.; Riccardi, Daniela M. R.; Lira, Fabio S.; Batista, Miguel L.; Seelaender, Marília
Abstract: Background: Cachexia is a systemic syndrome leading to body wasting, systemic inflammation, and to metabolic chaos. It is a progressive condition, and little is known about its dynamics. Detection of the early signs of the disease may lead to the attenuation of the associated symptoms. The white adipose tissue is an organ with endocrine functions, capable of synthesising and secreting a plethora of proteins, including cytokines, chemokines, and adipokines. It is well established that different adipose tissue depots demonstrate heterogeneous responses to physiological and pathological stimuli. The present study aimed at providing insight into adipocyte involvement in inflammation along the progression of cachexia. Methods: Eight‐weeks‐old male rats were subcutaneously inoculated with a Walker 256 carcinosarcoma cell suspension (2 × 10 7 cells in 1.0 mL; tumour‐bearing, T) or Phosphate‐buffered saline (control, C). The retroperitoneal, epididymal, and mesenteric adipose pads were excised on Days 0, 7, and 14 post‐tumour cell injection, and the adipocytes were isolated. Results: Mesenteric and epididymal adipocytes showed up‐regulation of IL‐1β protein expression and activation of the inflammasome pathway, contributing for whole tissue inflammation. The stromal vascular fraction of the retroperitoneal adipose tissue, on the other hand, seems to be the major contributor for the inflammation in this specific pad. Conclusion: Adipocytes seem to play a relevant role in the establishment of white adipose tissue inflammation, through the activation of the NF‐κB and inflammasome pathways. In epididymal adipocytes, induction of the inflammasome may be detected already on Day 7 post‐tumour cell inoculation.